Clinical impact of a multifaceted intervention aimed at decreasing distress in people living with dementia: evaluating the Reconnect program - Baird, Cheryl; Miller, Hannah; Hoti, Kreshnik; Hughes, Jeffery (Frontiers in Psychiatry, 2023)
Background To better meet the needs of people living with advanced dementia, Orchard Care Homes, United Kingdom have established an enhanced person focused program, namely the Reconnect program, which provides an enriched psycho-social care to enhance peoples’ quality of life and well-being. Here we aimed to review the impact of this program on people living with dementia. Methods In this study the implementation of the Reconnect program was evaluated for two six-month periods (April–September 2020 and April–September 2021). The focus of this evaluation was on three key interventions: increasing meaningful occupation and engagement; improving pain identification and management, and reducing constipation. The Reconnect program was conducted in a single for-profit care home. It involved residents with complex dementia needs who previously not responded to support in alternative settings or found previous care ineffective in relieving their distress and reducing risks they pose to themselves or others. Results A total of 24 people participated in the program during this evaluation. We observed a substantial increase in engagement in meaningful activity per person, including an increase of outdoor access to fresh air. Pain management improved as evidenced by more standardized pain assessments using the PainChek system and coverage of people with either regular and/or “when required” pain management. Constipation relief also improved. For the two comparison periods, distress responses per resident reduced from 14.5 to 10.6 events and use of regular pain relief increased from 21.7 to 48.1%. Use of “when required” benzodiazepine halved from 6 months average of 46 to 23.2 doses given. Benzodiazepine dose reductions increased from 13.3 to 31.8%, while cessations increased from 20 to 50%. We also observed a reduction from 76.3 to 56.3% in antipsychotic use. Their dose reductions increased from 8.3 to 40% and drug cessation was made in 30% of people using antipsychotics (compared to the first period in which no medication cessation was observed). A 91.7% reduction (i.e., from 36 to 3 events) in safeguarding events related to behaviors was also observed. Conclusion Introduction of the Reconnect program, through its interventions focused on meaningful activity engagement, pain management and constipation relief resulted in substantial improvements related to people’s distress, safeguarding and psychotropic use.